Problem and pro-social behaviour among adolescents living with HIV/AIDS and perception of healthcare workers on available medical and social support in Sokoto, northern Nigeria - Ezenwoko, Ahunna Z.; Raji, Mansur O.; Oche, Mansur O.; Oladigbolu, Remi A.; Kwaido, Asiya M. (International Journal Of Community Medicine And Public Health, 2024)
Background: Adolescents living with HIV/AIDS (ALHIV) are likely to have behavioural, social, cognitive, and emotional problems. Early detection and treatment of these psychological issues in ALHIV is precarious to comprehensive HIV management. This study aimed to assess problem and pro-social behaviour among and to identify available health facility and social supports for ALHIV in Sokoto State, Nigeria. Methods: A cross sectional study with mixed methods of data collection was conducted among 236 adolescent- caregiver pairs. Key informant interviews were conducted among four health care workers. Quantitative data were analyzed using IBM SPSS version 23 while content analysis along thematic lines was done for qualitative data. Results: Mean age of adolescents was 14.6±2.2 years while mean age of caregivers was 37.9±7.2 years. Prevalence of pro-social behaviour among ALHIV was 6.4% (self- report) and 15.2% (caregiver report). Seventy-eight (33.1%) caregivers reported peer problems and 15 (6.4%) emotional problems among their ALHIV. Based on self-report, 160 (67.8%) ALHIV reported experiencing peer problems and 3 (1.8%) emotional problems. Eleven (4.7%) adolescents reported having low social support, 136 (57.6%) had moderate and 89 (37.7%) high social support. Viral suppression showed significant association with SDQ scores. Conclusions: The Sokoto State Ministry of Health and other organizations supporting HIV programs should ensure community enlightenment programs on HIV in order to reduce stigma associated with the disease.